Disclosing diversity of exopolysaccharide-producing lactobacilli from Spanish natural ciders. (April 2018) - Puertas, Ana Isabel; Ibarburu, Idoia; Elizaquivel, Patricia; Zuriarrain, Andoni; Berregi, Iñaki; López, Paloma; Prieto, Alicia; Aznar, Rosa; Dueñas, María Teresa
Abstract: Lactic acid bacteria (LAB) are naturally occurring bacterial populations in traditional cider from the Basque Country (Spain), which is spontaneously fermented without starters. Some LAB are able to produce exopolysaccharides (EPS) thus causing viscosity, a cider spoilage called "ropiness" or "oilness". A total of 41 isolates recovered between 1992 and 2009 from ropy ciders of different cider factories were included in the present study. Identification by 16S rRNA gene sequencing, biochemical traits (API), RAPD-PCR using four universal primers (M13, M13V, P1 and P2) and 16S-23S ISRs amplification profiles revealed that the spoiler species were L. collinoides, L. diolivorans, L. sicerae and L. suebicus. EPS production in L. collinoides and L. sicerae strains approached by PCR amplification of eps genes encoding for homopolysaccharide and heteropolysaccharide revealed that these strains synthesize heteropolysacccharides and in addition, L. collinoides CUPV231 synthesizes a 2-branched (1, 3)-β-D-glucan. The molecular weight of their EPS determined by HP-SEC revealed the presence of three polymers with average molecular weights (MW ) of around 10 6  g/mol, 10 4  g/mol and 10 3  g/mol. The middle-weight fraction was the most abundant except in L. sicerae CUPV261 which mainly produced the high Mw polymer. Highlights: EPS producing strains from Spanish ropy cider were identified by molecular methods. RAPD profiles analysis assured the correct ascription of isolates to LAB species. L. collinoides, L. diolivorans, L. suebicus and L. sicerae were the EPS producers. EPS structural analysis revealed that L. collinoides CUPV231 produces HoPS and HePS. Molecular weight of surface polysaccharides was determined by HP-SEC.